Ritual Symbolism and Culinary Practice in Winter Solstice Folklore: A Comparative Study in East Asia - Kobayashi, Fumihiko (UIN Sunan Gunung Djati Bandung, 2025)
Purpose: This study investigates the symbolic and ritual functions of winter solstice food traditions—particularly red-bean porridge, wontons, and pumpkin-based dishes—in East Asian cultures (China, Korea, and Japan). The research aims to uncover how these culinary customs, rooted in folklore and seasonal cosmology, function as embodied responses to the liminality of the winter solstice, a period historically viewed as both auspicious and dangerous. Methodology: The study uses a qualitative-historical research approach, drawing from the disciplines of folklore, cultural anthropology, and historical ethnography. Data were collected through close readings of primary sources such as Jingchu Suishiji, Engishiki, and classical diaries, alongside secondary analyses by modern East Asian folklorists and scholars. Victor Turner’s theory of liminality serves as the core analytical framework, with a comparative lens applied across the three national contexts. Findings: The research finds that solstice food customs—like red-bean porridge in China and Korea, and pumpkin dishes in Japan—serve not merely as seasonal nourishment but as apotropaic rituals aimed at warding off evil spirits and maintaining social cohesion. These culinary traditions reflect broader cosmological beliefs rooted in agricultural cycles, yin-yang theory, and mythological storytelling. Furthermore, the study highlights the intergenerational transmission of these customs through oral and embodied practices, while also identifying vulnerabilities posed by urbanization and cultural erosion. Implications: The findings contribute to the growing field of intangible cultural heritage studies by positioning solstice food rituals as vital forms of vernacular cosmology and community resilience. Originality and Value: This research offers an original contribution by foregrounding food as a cosmological medium—an epistemological tool that allows communities to ritualize astronomical transitions. It departs from conventional studies of solstice marked through monuments or festivals, and instead emphasizes domestic, edible rituals. By theorizing the hearth as a cosmological site, the study invites rethinking cultural astronomy through taste, tactility, and seasonal embodiment, providing new intersections between folklore, anthropology, and food studies.